The association between different molecular weights of hyaluronic acid and CHAD, HIF-1 alpha, COL2A1 expression in chondrocyte cultures - Yaşar Şirin, Duygu; Kaplan, Necati; Yılmaz, İbrahim; Karaarslan, Numan; Özbek, Hanefi; Akyuva, Yener; Kaya, Yasin Emre; Öznam, Kadir; Akkaya, Nuray; Güler, Olcay; Akkaya, Semih; Mahiroğulları, Mahir (Spandidos Publications Ltd, 2018)
The aim of the present study was to investigate the effects of three different formulations of hyaluronic acid (HA): Low molecular weight (MW) Sinovial One((R)), medium MW Viscoplus((R)) and high MW Durolane((R)), on chondrocyte proliferation and collagen type II (COL2A1), hypoxia-inducible factor 1 alpha (HIF-1 alpha) and chondroadherin (CHAD) expression in primary chondrocyte cultures. Standard primary chondrocyte cultures were established from osteochondral tissues surgically obtained from 6 patients with gonarthrosis. Cell morphology was evaluated using an inverted light microscope; cell proliferation was determined with a MTT assay and confirmed with acridine orange/propidium iodide staining. Levels of CHAD, COL2A1 and HIF-1 alpha expression were assessed using specific TaqMan gene expression assays. The results demonstrated the positive effect of HA treatment on cell proliferation, which was independent from the MW. COL2A1 expression increased in the medium and high MW HA treated groups. It was observed that HIF-1 alpha expression increased in the high MW treated group alone. CHAD expression increased only in the medium MW HA treated group. Evaluation of gene expression revealed that levels of expression increased as the duration of HA application increased, in the medium and high MW HA treated groups. In terms of increased viability and proliferation, a longer duration of HA application was more effective. Taken together, it may be concluded that the administration of medium and high MW HA may be a successful way of treating diseases affecting chondrocytes in a clinical setting.
WOS: 000431850300018
PubMed ID: 29849772
Keywords: Chondroadherin; Collagen Type II; Hypoxia Inducible Factor 1 Alpha; Hyaluronic Acid; Chondrocytes